Long Noncoding RNAs and Stress Response in the Nucleolus - Sergei A. Pirogov; Vladimir A. Gvozdev; Mikhail S. Klenov (Cells, 2019)
Long noncoding RNAs (lncRNAs) perform diverse functions in the regulation of cellular processes. Here we consider a variety of lncRNAs found in the ribosome production center, the nucleolus, and focus on their role in the response to environmental stressors. Nucleolar lncRNAs ensure stress adaptation by cessation of resource-intensive ribosomal RNA (rRNA) synthesis and by inducing the massive sequestration of proteins within the nucleolus. Different cell states like quiescence and cancer are also controlled by specific lncRNAs in the nucleolus. Taken together, recent findings allow us to consider lncRNAs as multifunctional regulators of nucleolar activities, which are responsive to various physiological conditions.